Retrospective analysis of antimicrobial resistance of Salmonella spp. isolated from livestock and its environment in Thailand - Lertwatcharasarakul, Preeda; Phatthanakunanan, Sakuna; Tulayakul, Phitsanu (Frontiers in Veterinary Science, 2025)
IntroductionA retrospective study of non-typhoidal Salmonella isolation from poultry and pig farms in Nakhon Pathom and Suphan Buri provinces was conducted from 2008 to 2015. The aim of study was to examine the prevalence of antimicrobial resistance and class I integrons related to gene resistance of Salmonella in livestock and its environment.MethodsA total of 636 Salmonella isolates was collected from livestock and environmental samples. The isolates included 1.42% S. Typhimurium, 4.40% S. Enteritidis, and 1.26% S. Virchow; however, neither S. Infantis nor S. Hadar were found. All Salmonella isolates was tested for antimicrobial susceptibility and minimum inhibitory concentrations (CLSI Vet03-S2 2014, NCCLS standard).ResultsThe top three drug resistances were to cephalexin, gentamicin, and amoxicillin. S. Typhimurium showed resistance rates of 100%, 100%, and 22.22% to these antibiotics, respectively; S. Enteritidis showed resistance rates of 100%, 100%, and 90.91%; and S. Virchow revealed resistance at the rates of 50%, 50%, 12.50%, respectively. The conserved segment integrase 1 and gene cassette were found by polymerase chain reaction (PCR) in all serotypes. The resistance gene of aadb, IntI1, aac(6′)-la, aac(6′)-lb, blaPSE-1, CmlA, Sul, dfrA1, A10 and A12 were not detected from S. Typhimurium and fewer resistance genes were detected when compared to the other two subtypes.DiscussionThese findings could be used to set up the prevention and control strategies for addressing future antimicrobial resistance of Salmonella, which remains a major food safety concern.